STATISTICAL MODELING OF QUARRYING ACTIVITIES AND THEIR IMPACT ON RESIDENTS’ SATISFACTION - Domingues, Jefferson M.; Miranda, Vania F. L.; Rezende, Denise C.; Lares, Yara S.; Ferreira, Saulo R.; de Oliveira, Izabela R. C. (UI Scholars Hub, 2020)
This research aims to analyse the impact of quarrying on the health and perception of neighbouring communities. A standard questionnaire survey was conducted to collect data from quarry neighbours in a residential neighbourhood located in the city of Lavras, Minas Gerais, Brazil. Residences were distributed based on proximity to a quarrying company, resulting in three distances divided by three equally distant radii, named as Area I (closest to the quarrying company at 630 m), Area II (730 m), and Area III (farthest from the quarrying company at 830 m). Data gathered from 177 residents were analysed with logistic regression models. Results indicated significant differences between Areas I and III, and as expected, disturbances decreased as the distance from the quarrying company increased. Area III residents provided the most favourable response to quarrying activities, and the noise was the main complaint in the three areas. The number of residents who complained about noise was 91, 77, and 63% for Areas I, II, and III, respectively. The employed method can be used satisfactorily for neighbourhood impact evaluations, considering personal experiences, human perception, and seasonal effects.